THE INFLUENCE OF SHOPPING MALLS ON YOUTH LIFESTYLE - Firzal, Yohannes; Syahrani, Kartika (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
Shopping malls can influence adolescents' lifestyle. Adolescents' ability to adjust lifestyle has assumed dynamism in the social order system and a symbol of identity. In this context, the relationship between adolescent lifestyles and shopping malls is interesting to investigate how the dimensions of youth lifestyle influence and shopping mall attractiveness indicators identify adolescent visitors' characteristics. By using the incidental sampling technique, this quantitative research data involved 97 adolescents as respondents through interview and questionnaire methods, secondary data support, and multiple regression methods consisting of 5 independent variables, namely convenience, comfort, diversity, entertainment, luxury and essence of the mall and one lifestyle dependent variable. Two data analysis techniques; cross-table analysis of respondent characters and statistical analysis using SPSS software to support study in the Linkert Scale, followed by validity testing, reliability testing, classical assumption test, multiple regression test, t-test (partial), F test (simultaneous) and coefficient determination. The analysis found that the comfort variable is the most significant variable that impacts adolescent lifestyle. Therefore, there needs to be intensive supervision of mall activities with a high level of convenience to anticipate deviant actions that are feared to harm teenage lifestyles